2012
DOI: 10.5194/acp-12-11095-2012
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous chlorine activation on stratospheric aerosols and clouds in the Arctic polar vortex

Abstract: Abstract. Chlorine activation in the Arctic is investigated by examining different parameterizations for uptake coefficients on stratospheric aerosols, high-resolution in-situ measurements and vortex-wide satellite observations. The parameterizations for heterogeneous chemistry on liquid aerosols are most sensitive to temperature with the reaction rates doubling for every 1 K increase in temperature. However, differences between the currently available parameterizations are negligible. For Nitric Acid Trihydra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 68 publications
8
95
0
Order By: Relevance
“…An alternative parameterisation for reactions on liquid particles was reported by Shi et al (2001), which results however in a heterogeneous reactivity very close to the one employed here (e.g. Wegner et al, 2012).…”
Section: The Submodel Pscmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative parameterisation for reactions on liquid particles was reported by Shi et al (2001), which results however in a heterogeneous reactivity very close to the one employed here (e.g. Wegner et al, 2012).…”
Section: The Submodel Pscmentioning
confidence: 99%
“…They concluded that the surface area provided by PSCs did not significantly impact chlorine activation rates in these both winters. Wohltmann et al (2013) showed, based on simulations of the Arctic winter 2009/2010 with the Lagrangian model ATLAS, that liquid aerosols alone allow to explain the observed mixing ratios of active chlorine and ozone from Microwave Limb Sounder (MLS), Atmospheric Chemistry Experiment -Fourier Transform Spectrometer (ACE-FTS) and in situ measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some recent studies have suggested that liquid PSCs play a dominant role in activating chlorine (e.g., Wegner et al, 2012;Wohltmann et al, 2013), the formation temperatures of solid nitric acid trihydrate (NAT, Hanson and Mauersberger, 1988) and ice particles remain convenient thresholds for the initiation of chlorine activation processes. In this study, we examine daily 12:00 UT minimum temperatures and calculations of area with temperatures below PSC thresholds (henceforth T min and A PSC , respectively).…”
Section: Temperature and Vortex Diagnosticsmentioning
confidence: 99%
“…The relative roles and temperature dependencies of surface reactions on and in water ice, nitric acid trihydrate ice, and supercooled liquid sulfuric acid−water−nitric acid and binary sulfuric acid−water particles at background levels have been research topics since the late 1980s, and some important questions have recently reemerged. Some recent studies have suggested that heterogeneous chemistry taking place on background particles of sulfuric acid and water is sufficient to explain nearly all of the chlorine activation (17)(18)(19) and ozone losses in both the Arctic and Antarctic (17) without any need for temperatures below −78°C or formation of polar stratospheric clouds, which would represent a major change in understanding. The potential for liquid binary aerosols to play some role in ozone loss under cold conditions was first identified decades ago (20,21).…”
Section: Lower Stratospheric Chemistrymentioning
confidence: 99%